Mucosal vaccine delivery: A focus on the breakthrough of specific barriers - Mengwen Huang; Miaomiao Zhang; Hongbin Zhu; Xiaojiao Du; Jun Wang (Acta Pharmaceutica Sinica B, 2022)
Mucosal vaccines can effectively induce an immune response at the mucosal site and form the first line of defense against microbial invasion. The induced mucosal immunity includes the proliferation of effector T cells and the production of IgG and IgA antibodies, thereby effectively blocking microbial infection and transmission. However, after a long period of development, the transformation of mucosal vaccines into clinical use is still relatively slow. To date, fewer than ten mucosal vaccines have been approved. Only seven mucosal vaccines against coronavirus disease 2019 (COVID-19) are under investigation in clinical trials. A representative vaccine is the adenovirus type-5 vectored COVID-19 vaccine (Ad5-nCoV) developed by Chen and coworkers, which is currently in phase III clinical trials. The reason for the limited progress of mucosal vaccines may be the complicated mucosal barriers. Therefore, this review summarizes the characteristics of mucosal barriers and highlights strategies to overcome these barriers for effective mucosal vaccine delivery.